Status of Glycosylated Hemoglobin and Lipid Profile in Gestational Diabetes Patients - G S R*, Kedari (Recent Research in Science and Technology, 2010)
Aim: The exact alterations in lipid profile as well as the levels of glycosylated hemoglobin in gestational diabetes are still not clearly documented. Methods: To add a new insight to the question, levels of lipid profile parameters and the levels of glycosylated hemoglobin were studied in patients with gestational diabetes and compared to controls. Results: Fasting plasma glucose levels, Plasma glucose levels 1 hr and 2 hrs after 75 gm oral glucose administration (Oral Glucose Tolerance Test) were significantly higher in cases than in controls. Glycosylated hemoglobin was significantly higher in cases than in controls. It was observed that there was a significant increase in serum triglycerides in cases with gestational diabetes when compared to controls. Conclusion: The results of our study suggests that abnormal glucose levels, Glycosylated hemoglobin and serum triglycerides plays an important role in gestational diabetes patients and therefore extensive studies are required. Early diagnosis of gestational diabetes provides safe baby and motherhood and in particular it will reduce the severity of complications and mainly fetal and maternal morbidity and mortality.